Exploring the relationship between financial literacy, risk-taking propensity and entrepreneurship in Spanish undergraduates - Diéguez-Soto, Julio; Molina-García, Antonio; Martínez-Alonso, Rubén; Martínez-Romero, María José (My University, 2022)
This article uses covariance-based structural equation models in a sample of 568 Spanish undergraduates to provide evidence on the impact of financial literacy (measured through its three dimensions, that is, financial knowledge, attitude, and behaviour) on entrepreneurial intention through the mediating role of the risk-taking propensity. The results show that: (i) financial knowledge has an indirect positive impact; (ii) financial attitude has an indirect negative impact; (iii) financial behaviour has a positive impact both directly and indirectly. These findings are highly relevant in demonstrating the mechanism that explains the relationship between financial literacy and entrepreneurial intention considering the role of risk-taking propensity, an important channel to promote youth entrepreneurship.
Keywords: Finanzas; Emprendimiento; financial literacy; entrepreneurship